Factors affecting teacher workload in low-enrollment schools: a survey of Sarawak state schools, Malaysia - Junaidi Asman; Gurumoorthy Poobalan; Mazni Mustapha; Roslee Talip; Rosna Padan; Sukuneswari Kaliappan; Syd Alimulhakim Syd Ali; Aishah Mohd Aris (Human Resource Management Academic Research Society, 2023)
Student achievement and educator motivation could be impacted by teacher workload. The future of the nation is affected by student achievement. Educators in today's world are dealing with a greater variety of challenges. This article's purpose is to explore the factors that influence the workload of teachers in low-enrollment schools. To obtain data, a questionnaire was distributed to students in low-enrollment schools in Sarawak. A total of 159 academic teachers from a low enrollment school responded to the Google Form questionnaire. According to the findings of the study, the factor of additional teacher duties contributes the most to the workload of teachers in low enrollment schools, followed by the factor of limited school infrastructure and a shortage of teachers. In addition, the unbalanced staffing policies and inequality in administrative leadership are the fourth and fifth factors that affect the workload of teachers in schools in less enrollment. In addition, the shift in educational culture, teachers' clerical duties that limit their time for preparing teaching materials, careless school management, teachers' task instructions that are not planned by the school, the increase in online systems and educational applications that require teachers to enter data, and the inadequate time allotted to complete tasks everything contribute to the increased workload of teachers. In addition, the researcher proposed several solutions to the problem of teacher workload. The implications of this study provide researchers and education policy practitioners with the knowledge and direction necessary to ensure that the workload of teachers, particularly in low-enrollment schools, continues to be in accordance with school transformation standards between 2021-2025.